Urban Farming as an Alternative in Realizing Sustainable City Development in Indonesia - Armansyah, Armansyah; Giyarsih, Sri Rum; Fathurohman, Apit; Soetrisno, Ade Latifa; Zaelany, Andy Ahmad; Setiawan, Bayu; Saputra, Dani; Haqi, Muamar; Lamijo, Lamijo (Jurnal Kawistara, 2024)
Urban farming has been associated with sustainable living in urbanized areas. However, theinterconnection between the two need further studies. Alternatives for promoting sustainable living is especially in important in Indonesia because urbanization in the country is expanding, while the area of productive agricultural land is decreasing. The limited spaces become a challenge for urban residents that need land for settlements, planting, green open spaces, spaces for interaction and socializing, and recreation. Therefore, urban farming presents an alternative in answering the problems caused by urbanization. This research aims to explore the interconnection of urban farming and urbanization in an effort to realize sustainable urbandevelopment. This research is the initial part of an effort to create an integrated model of urban farming for urbanization for food security for urban residents (2023-2025) in the Innovation Research for Advanced Indonesia (RIIM) scheme. This study uses qualitative methods withinformants as a sample data source. Informants were selected using a purposive sampling technique, totaling 30 urban farming actors, with details of 10 informants from Palembang City, 10 from Bandung City, and 10 from Denpasar City. Collection through the stages of observation, in-depth interviews, and documentation. Data analysis uses the Miles and Hubberman Model with three stages, namely data reduction, data display, and drawing conclusions. The data validity test technique uses triangulation with the cross-check method. The results of the analysis found an interrelation between urban farming and urbanization in nine dimensions, namely; economy,social, environment, health, culture, food, education, tourism, and technology. The interrelationship between urban farming and urbanization is positive, which means that the positive impact of urban farming has an indication of minimizing the negative impact of urbanization. In addition, this interrelation is also relevant to the three principles of sustainable development, namely having the function of controlling environmental impacts to a minimum, economic and social functions.